Star Wars The Old Republic. - Glasser, AJ.
How the planets in BioWare's new Star Wars MMO begin with a color.
Keywords: BioWare Corp; Star Wars: The Roleplaying Game (Game); Star Wars films Video games; Massively multiplayer online (MMO) games